2015
DOI: 10.1186/s40163-015-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Introducing intelligence-led conservation: bridging crime and conservation science

Abstract: The multidisciplinary nature of conservation science lends itself to be a unique area of study for those interested in crime science. In particular, crime scientists can contribute to the development, implementation, and evaluation of crime and intelligence analysis that address wildlife crime. Crime and intelligence analysis has gained significant attention from conservationists in recent years due to the increasing accessibility and capabilities of various forms of information technology. This has led to sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
0
25
0
2
Order By: Relevance
“…It allows law enforcement agencies to allocate resources more efficiently for crime prevention, reduction and disruption, including by targeting investigations toward serious offenders (Maguire & John, 2006). In fact, intelligence‐led policing has been successfully applied to address wildlife crime in Uganda (e.g., Moreto, 2015; Moreto et al, 2017), as well as other environmental crimes, such as the illegal export of hazardous waste in the United Kingdom (Gibbs, McGarrell, & Sullivan, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It allows law enforcement agencies to allocate resources more efficiently for crime prevention, reduction and disruption, including by targeting investigations toward serious offenders (Maguire & John, 2006). In fact, intelligence‐led policing has been successfully applied to address wildlife crime in Uganda (e.g., Moreto, 2015; Moreto et al, 2017), as well as other environmental crimes, such as the illegal export of hazardous waste in the United Kingdom (Gibbs, McGarrell, & Sullivan, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One way to improve the effectiveness of antipoaching patrols in PAs is by collecting information to inform where park guards should focus their efforts (Fang et al, 2017; Linkie et al, 2015; Moreto, 2015), given that patrols have limited opportunity to detect offenders (Critchlow et al, 2017; Moreto & Lemieux, 2015). The use of community‐based information, both paid informants and information that is volunteered, is a widespread element of criminal investigations within law enforcement and intelligence communities (Billingsley, Nemitz, & Bean, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a need to gain a better understanding of the lived experiences of those involved in implementing militarised conservation, notably rangers. A growing number of researchers are engaged in this task ( Massé et al, 2017a , Massé et al, 2017b ; Moreto, 2015a , Moreto, 2015b ; Moreto et al, 2015 ; Moreto et al, 2017 ; Gore, 2017 ). Not claiming to speak for rangers, these researchers instead offer avenues to draw attention to the problems and challenges that rangers face, and their own concerns and criticisms of militarised conservation.…”
Section: Focusing On the Symptoms Not The Root Causes Of Poachingmentioning
confidence: 99%
“…However, crime scientists also have much to offer in examining wildlife crimes (cf. Moreto 2015). Specifically, it has been suggested that conservation efforts might be improved by analyzing various wildlife crimes in a manner akin to traditional crime types (e.g.…”
Section: Introductionmentioning
confidence: 99%